OPTIMIZATION OF AN INTRA-SUPPLY CHAIN SYSTEM WITH UNRELIABLE PRODUCTION FACILITY - Chiu, Singa Wang; Chen, Hsin-Mei; Lin, Hong-Dar; Chiu, Yuan-Shyi Peter (Journal of Applied Engineering Science, 2018)
Optimization of a manufacturer-retailer integrated type of intra-supply chain system considering unreliable production facility is explored in this study. It is assumed that a producer of consumer goods has its own sales offices, and during the fabrication process, both equipment breakdown and production of nonconforming goods seem inevitable. To explicitly address such a real intra-supply chain problem, we incorporate end products transportation cost and sales office’s stock holding cost into a prior study (Chiu [1]) with the objective of deriving the optimal fabrication runtime. Solution to the problem is obtained through the use of mathematical modeling, optimization techniques, and a proposed recursive algorithm. Applicability of research result and sensitivity analyses are demonstrated thru numerical example.
Keywords: Optimizer; manufacturer-retailer integrated system; optimal fabrication runtime; unreliable facility; intra-supply chain system; rework; multiple shipments